Amanuta: a case of ilustrated books for children - Pavez, Ana María (Base Diseño e Innovación, 2016)
Amanuta is a publishing house mainly of illustrated books for children formed fifteen years ago with the purpose of giving value to, and reinterpreting, myths, traditions, legends, stories and other expressions to make them known to the children in Chile and Latin America, using modern and creative language and illustrations. It has published more than one hundred titles, and each one of them has been a new challenge that we have undertaken, always looking for the books to have innovative themes, illustrations, designs, formats, etc. This has become increasingly difficult since in a globalized world where the illustrated books for children are on the rise, it is a great challenge to make novel proposals. But with effort we have been able to make ourselves room in the domestic market, where most Chilean school libraries have Amanuta's books and we see how, year after year, there are more children who read them. We have also been able to reach Mexico, Colombia, Argentina, Guatemala and the United States.